Examining variation in the leaf mass per area of dominant species across two contrasting tropical gradients in light of community assembly - Neyret, M.; Bentley, L.P.; Oliveras Menor, I.; Marimon, B.S.; Marimon-Júnior, B.H.; Almeida de Oliveira, E.; Barbosa Passos, F.; Castro Ccoscco, R.; Dos Santos, J.; Reis, S.; Morandi, P.S.; Rayme Paucar, G.; et al. (John Wiley and Sons, 2016)
Understanding variation in key functional traits across gradients in high diversity systems and the ecology of community changes along gradients in these systems is crucial in light of conservation and climate change. We examined inter- and intraspecific variation in leaf mass per area (LMA) of sun and shade leaves along a 3330-m elevation gradient in Peru, and in sun leaves across a forest–savanna vegetation gradient in Brazil. We also compared LMA variance ratios (T-statistics metrics) to null models to explore internal (i.e., abiotic) and environmental filtering on community structure along the gradients. Community-weighted LMA increased with decreasing forest cover in Brazil, likely due to increased light availability and water stress, and increased with elevation in Peru, consistent with the leaf economic spectrum strategy expected in colder, less productive environments. A very high species turnover was observed along both environmental gradients, and consequently, the first source of variation in LMA was species turnover. Variation in LMA at the genus or family levels was greater in Peru than in Brazil. Using dominant trees to examine possible filters on community assembly, we found that in Brazil, internal filtering was strongest in the forest, while environmental filtering was observed in the dry savanna. In Peru, internal filtering was observed along 80% of the gradient, perhaps due to variation in taxa or interspecific competition. Environmental filtering was observed at cloud zone edges and in lowlands, possibly due to water and nutrient availability, respectively. These results related to variation in LMA indicate that biodiversity in species rich tropical assemblages may be structured by differential niche-based processes. In the future, specific mechanisms generating these patterns of variation in leaf functional traits across tropical environmental gradients should be explored.
Keywords: Variation (astronomy); Ecology; Biology; Community structure; Geography; Botany; https://purl.org/pe-repo/ocde/ford#1.06.09